(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To assess the medication adherence of epilepsy patients in the community of Hai Phong city in 2023. Method: A cross-sectional descriptive study was conducted using a convenience sampling method. A self-administered questionnaire was employed to determine the level of medication adherence among epilepsy patients. Results: The average age of the epilepsy patients was 42.6 years. The majority of patients had been living with the condition for over 10 years, accounting for 86.3% of the sample. Approximately 7.4% of patients reported occasionally forgetting to take their medication, and 1.5% of patients had missed medication on one or more days in the past two weeks. Around 9.8% of patients expressed frustration with the daily requirement to take medication. Furthermore; 21.6% of patients occasionally found it difficult to remember the medications they were prescribed, while 3.4% consistently struggled with remembering their medication regimen. Conclusion: The overall medication adherence among epilepsy patients was relatively high, with 8.8% showing low adherence, 46.1% exhibiting medium adherence, and 45.1% demonstrating high adherence